Tailored nanoparticles by wet chemical particle technology: From lab to pilot scale - Flegler, Andreas; Wintzheimer, Susanne; Schneider, Michael; Gellermann, Carsten; Mandel, Karl (Handbook of Nanomaterials for Industrial Applications, 2018)
In this chapter the merits of employing nanoparticles synthesized in dispersion via bottom-up wet chemistry in advanced materials are pointed out. Yet, the reality shows that there is a lack of nanoparticles made this way in “real-life” applications. Potential reasons for that are briefly outlined, pointing towards the challenges of upscaling of wet chemical nanoparticle syntheses. In four sample cases of nanoparticle synthesis upscaling from milligram to multigram and kilogram scale, the encounter of these challenges is described and examples are given as to how they could be overcome. In the view of the authors, these examples demonstrate that there is exciting science and engineering behind wet chemical nanoparticle synthesis upscaling. Not only with respect to achieving “real-life” applications, but also with respect to new scientific discoveries, this field of colloidal engineering is worth to be pursued a lot more in future.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Bottom-up; Colloid chemistry; Colloidal engineering; Large scale nanoparticle synthesis; Nano chemistry; Nanomaterials; Nanoparticles; Pilot scale; Upscaling